Dampak Soft Diplomacy Arab Saudi terhadap Budaya Islam di Indonesia - Ardhian, Michael (Peneliti.net, 2025)
This research was made to find out how much impact Saudi Arabia''s Soft Diplomacy to Islamic Culture in Indonesia.This research uses secondary data. In this study, researchers used secondary data from media such as internet sites and Indonesian government sites, electronic newspapers, and journals related to the Impact of Saudi Arabia''s Soft Diplomacy on Islamic Culture in Indonesia. Meanwhile, the data collection technique in this research is qualitative. Qualitative research is a continuous research process. This research is a qualitative descriptive research. The return of scholars who studied in Saudi Arabia to Indonesia certainly brought not only the influence of Islam to Indonesia, but also brought the influence of Indonesian culture to Saudi Arabia even though the people of Saudi Arabia did not accept it as a whole, but combined it with local wisdom owned by Saudi Arabia. Cultural diplomacy is an effort that countries make to fight for their national interests for cultural aspects. The relationship between Saudi Arabia and Indonesia is a long-standing relationship, unofficially the relationship between Saudi Arabia and Indonesia has been established since the first century of hijriyah and officially on May 1, 1950, in the course of the relationship between the two countries there has been a lot of cooperation that has been agreed upon and one of them is in the social and cultural fields.